The quality of the services perceived by the students of the National University of Chimborazo of the city of Riobamba - Ecuador - Saltos Aguilar, Wilson Manuel (2017)
The present research work has identified the risk and success factors of the quality of the educational services of the students of the National University of Chimborazo and the impact of the quality factors of the services perceived. If from the 45 factors we can improve on 12 factors that are: comfort of the classroom, comfort of offices, cleanliness of the toilet, answer's capacity, quickness of care, attention to complaints, student knows where to complain, useful information, campus safety, and teacher performance. It follows that there is a high probability that students will be satisfied with the services and recommend to the institution.